Treatment Strategies for Congenital Diaphragmatic Hernia: Change Sometimes Comes Bearing Gifts - Morini, Francesco; Lally, Kevin P.; Lally, Pamela A.; Crisafulli, Rosa Maria; Capolupo, Irma; Bagolan, Pietro (Frontiers in Pediatrics, 2017)
Objective: To report treatment strategies’ evolution and its impact on congenital diaphragmatic hernia (CDH) outcome. Design: Registry-based cohort study using the CDH Study Group database, 1995- 2013. Setting: International multicenter database Patients: CDH patients entered into the registry. Late presenters or patients with very incomplete data were excluded. Patients were divided into three Eras (1995-2000; 2001-2006; 2007-2013). Main outcome measures: Treatment strategies and outcomes. One way ANOVA, X2 test and X2 test for trend were used. A Sydak-adjusted p<0.0027 was considered significant. Prevalence or mean (standard error) are reported. Results: Patients: 8603; included: 7716; Era I: 2146; Era II: 2572; Era III: 2998. From Era I to Era III significant changes happened. Some severity indicators such as gestational age, prevalence of prenatal diagnosis and inborn patients significanltly worsened. Also treatment strategies such as the use of prenatal steroids and inhaled nitric oxide, age at operation, prevalence of minimal access surgery and the use of surfactant significantly changed. Finally, length of hospital stay became significantly longer and survival to discharge slightly but significantly improved, from 67.7% to 71.4% (p for trend 0.0019). Conclusions: Treatment strategies for patients registered since 1995 in the CDH Study Group significantly changed. Survival to discharge slightly but significantly improved.